أشر استراتيجيات إدارة الموارد البشرية إعداد كفإات القيادات الإدارية بسلطنة عمان: دعم الإدارة العليا متغيرا اعتداليا - Farida Said Moosa Al Balushi
The present study aims to assess the effect of human resource management strategies on preparing administrative competencies. The model of the study comprises a number of factors as independent variables, which are planning and forecasting strategy, selection and recruitment strategy, job analysis strategy, training and development strategy, and the dependent variable, is represented by the preparing administrative competencies. The study also aims to analyzing the impact of senior management is concerned with the relationship between human resource management strategies and the preparation of administrative competencies as moderator variables. To achieve the objective of the study, a quantitative approach to analyze the data was used, specifically a Confirmatory Factor Analysis (CFA) to assess the convergent and structural validity of the research model; and the structural equation modeling (SEM-AMOS) for testing the research hypotheses and objectives. The population of the study consisted of the Staff of the Ministry of Regional Municipalities and Water Resources, Sultanate of Oman. The survey was distributed to 550 participants (comprehensive sample). 231 questionnaires were valid for analysis. The results of the study show that all the investigated factors had a positive impact on the preparing administrative competencies as the data explained almost 74% of the effect, Except for a job analysis strategy. In addition, the selection and recruitment strategy had the greatest impact (34%); followed by the training and development strategy (30%); and finally, the Planning and forecasting strategy had the third effect as they represented (25%). It was also found that the sample supporting senior management support had a positive impact on the relationship between human resource management strategies and the preparation of administrative competencies, which would not have been in non-supportive senior management support. Based on the results of the current study, it is recommended that the Increasing interest in human capital because it is the active ingredient in the success of any operation, as well as realizing the importance of the role provided by top management.